2019
DOI: 10.1002/biot.201900130
|View full text |Cite
|
Sign up to set email alerts
|

BiP Inducer X: An ER Stress Inhibitor for Enhancing Recombinant Antibody Production in CHO Cell Culture

Abstract: Prolonged endoplasmic reticulum (ER) stress reduces protein synthesis and induces apoptosis in mammalian cells. When dimethyl sulfoxide (DMSO), a specific monoclonal antibody productivity (q mAb )-enhancing reagent, is added to recombinant Chinese hamster ovary (rCHO) cell cultures (GSR cell line), it induces ER stress and apoptosis in a dose-dependent manner. To determine an effective ER stress inhibitor, three ER stress inhibitors (BiP inducer X [BIX], tauroursodeoxycholic acid, and carbazole) are examined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Protein kinase RNA-like ER kinase (PERK), activating transcription factor 6 (ATF6), and the inositol-requiring enzyme-1α (IRE1α) are the major components of the UPR ( 8 , 9 ). The binding immunoglobulin protein (BiP) is a member of the heat shock protein (HSP) 70, and it is destined to assist in the maturation and folding of nascent proteins ( 10 ). When those proteins bind to the BiP, they are inactive.…”
Section: Unfolded Protein Responsementioning
confidence: 99%
“…Protein kinase RNA-like ER kinase (PERK), activating transcription factor 6 (ATF6), and the inositol-requiring enzyme-1α (IRE1α) are the major components of the UPR ( 8 , 9 ). The binding immunoglobulin protein (BiP) is a member of the heat shock protein (HSP) 70, and it is destined to assist in the maturation and folding of nascent proteins ( 10 ). When those proteins bind to the BiP, they are inactive.…”
Section: Unfolded Protein Responsementioning
confidence: 99%
“…The overexpression or co‐expression of chaperones is nowadays widely used as an approach to enhance recombinant protein expression [23,24]. Alternative strategies to enhance recombinant protein expression is the addition of small molecule additives to the culture media, for example, dimethyl sulfoxide [25–28]. The precise mode of action of these small molecule additives is unclear, but at least in mouse embryonic cells it was shown that DMSO can induce ER stress [29].…”
Section: Discussionmentioning
confidence: 99%
“…Before assembling into a tetramer, BiP maintains a binding state with the heavy-chain polypeptide. Once the light-chain polypeptide is lacking, the heavy chain will not be secreted outside the cell, causing the proteasome in the cell to be unable to degrade the heavy-chain polypeptides secreted to extracellularly; thus, the unit productivity of antibody is significantly reduced ( Vanhove et al, 2001 ; Ha et al, 2019 ). Therefore, excess light-chain polypeptides should be ensured to improve the expression of antibodies.…”
Section: Optimization Of Gene Sequences Of Antibodymentioning
confidence: 99%